JAMINAN KEPASTIAN HUKUM INVESTASI DI INDONESIA SETELAH BERLAKUNYA UNDANG-UNDANG NOMOR 6 TAHUN 2023 TENTANG CIPTA KERJA - Pandu Nugroho; M. Adib Ridwan Azizy (Smart Law Journal, 2023)
This writing discusses issues related to legal certainty for direct investment in Indonesia in the perspective of Law Number 25 of 2007 concerning Investment in the new Investment Regulations in Indonesia through Law Number 11 of 2020 concerning Job Creation ( hereinafter abbreviated as "UUCK"). The research method used in this study is Normative Juridical, based on secondary legal materials. The analysis in this article uses a legal approach (Statute Approach) and a conceptual approach (Conceptual Approach). The legal materials search technique uses library research techniques (Library Research) and research analysis uses qualitative analysis. The results of the author's analysis show that the government's role is very important in encouraging increased direct investment in Indonesia. To achieve this, legal certainty is the main point that must be emphasized and studied before making direct investment. On that basis, the government issued the Job Creation Law as an answer to problems related to guaranteeing legal certainty for investment in Indonesia.